#1**+2 **

Assuming that we have a right triangle with hypotenuse AB and legs AC and BC.....we have....

BC = sqrt [ AB^2 - AC^2] = sqrt [ 12^2 - 8^2 ] = sqrt [ 144 - 64 ] = sqrt [80] =

sqrt [ 16 * 5 ] = sqrt [16] * sqrt [5] = 4 sqrt [ 5]

However.....it's also possible that BC is the hypotenuse and AB and AC are legs

In that case

BC = sqrt [ AB^2 + AC^2 ] = sqrt [ 12^2 + 8^2 ] = sqrt [ 144 + 64 ] = sqrt [ 208 ] =

sqrt [ 16 * 13 ] = sqrt [ 16]* sqrt [ 13 ] = 4sqrt [ 13 ]

CPhill May 10, 2019